2015
DOI: 10.2215/cjn.05160514
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Modality and Mortality in the Elderly

Abstract: Background and objectives Identifying the appropriate choice between hemodialysis (HD) and peritoneal dialysis (PD) is an unresolved issue in elderly patients with ESRD, who are at high risk for death but have a low chance of receiving kidney transplantation.Design, setting, participants, & measurements Data on 13,065 incident dialysis Korean patients (age$65 years) receiving HD (n=10,675) or PD (n=2390) were obtained from the Korean Health Insurance dataset. Multiple statistical approaches, including the mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 40 publications
4
56
0
1
Order By: Relevance
“…In fact, in a recent meta‐analysis by Han et al, the mortality risk in elderly patients (aged ≥65 years) was significantly higher among those treated with PD compared to conventional HD. This increased risk of death was even more pronounced among those with diabetes and longer dialysis vintage . On the other hand, among younger patients (aged <65 years), PD has been shown to be associated with superior survival rates …”
Section: Survival By Modality: Specific Patient Subgroups and Interacmentioning
confidence: 99%
“…In fact, in a recent meta‐analysis by Han et al, the mortality risk in elderly patients (aged ≥65 years) was significantly higher among those treated with PD compared to conventional HD. This increased risk of death was even more pronounced among those with diabetes and longer dialysis vintage . On the other hand, among younger patients (aged <65 years), PD has been shown to be associated with superior survival rates …”
Section: Survival By Modality: Specific Patient Subgroups and Interacmentioning
confidence: 99%
“…Last year, Han et al (18) published their database study of 13,065 incident PD and HD Korean patients aged $65 years, showing a hazard ratio of 1.20 (95% confidence interval, 1.13 to 1.28) for poorer survival on PD. Their metaanalysis of 631,421 elderly patients in 15 nonrandomized studies showed a hazard ratio for PD over HD of 1.10 (95% confidence interval, 1.01 to 1.20).…”
Section: The Survival Battle Begins: Pd Versus Hdmentioning
confidence: 99%
“…However, studies comparing survival statistics with ever more complex analyses continue to be published. In this issue of CJASN, Han et al (3) have published an analysis from the Korean registry with an accompanying meta-analysis focusing on the survival of older patients on hemodialysis (HD) and peritoneal dialysis (PD). In such a multimorbid cohort burdened with other geriatric syndromes, mortality outcomes on dialysis are generally poor and will depend on many factors other than dialysis modality.…”
mentioning
confidence: 99%